Analysis of Wind-Sand-Load-Induced Dynamic Response of Transmission Tower-Line Systems - Zhuoqun Zhang; Jiashu Liu; Kangjie Shao; Peng Zhang (Shock and Vibration)
Sandstorms are a common natural phenomenon that has the potential to cause severe disruptions to civil infrastructure. However, the effect of sandstorms on transmission tower structures has not received much attention. This paper proposes the simulation of the wind-sand loads for the analysis of transmission tower structures under sandstorm excitation by superposing the wind loads and sand particle loads. The wind load is generated based on Kaimal fluctuating wind power spectrum and the harmonic superposition method, and the sand load is constructed based on the law of conservation of momentum and sandstorm classification. A transmission tower was modeled and simulated in SAP2000 to explore the dynamic response of the tower towards wind-sand loads. A comparison of wind-induced and wind-sand-induced responses shows that the structural dynamic responses of transmission towers due to the wind-sand effect are pronounced. Particularly, the maximum longitudinal displacements and axial forces increased greatly. The results showed that the sandstorm loads for transmission towers cannot be neglected, and more attention should be paid to the structural design of transmission towers to resist such loads.